Globally distributed teams: the effect of diversity on trust, cohesion and individual performance - Garrison, Gary; Wakefield, Robin L.; Xu, Xiaobo; `Kim, Sang Hyun (ACM SIGMIS Database: the DATABASE for Advances in Information Systems, 2010)
Globally distributed teams are becoming more common among organizations that seek to maximize knowledge creation and innovation for competitive advantage. Although they are becoming widely used among global organizations, distributed teams are creating an environment replete in cultural and functional diversity. Whereas synergy among members is desired, diversity is likely to hinder team cohesion and individual performance. Our study models and empirically tests the effect of perceptions of diversity on trust, cohesion, and individual performance in actual globally distributed teams. The results indicate that individual productivity is negatively influenced by the extent of diversity within a team; however, this liability may be restrained if an environment of trust is encouraged and team cohesion develops.